Regulation and Internet Access in Germany - Michael Reutter (Center for Economic Studies and ifo Institute (CESifo), 2001)
We explain the recent events in the German market for online access using a model of a regulated monopoly renting phone lines to retailers. Retailers offer either a linear or a flat tariff to consumers. Consumer heterogeneity leads to adverse selectiion. We show why market entry for flatrate firms is difficult under a linear wholesale tariff. With both a linear and a flat wholesale tariff the consumer market shows a mixture of tariffs as well. When marginal costs are zero it is optimal to have a wholesale flatrate only. However, marginal moves towards this equilibrium are not always welfare improving.
Keywords: 330; Internet; flatrate; adverse selection